(untitled) (Semiárida, 2020)
3 sectors were defined with different intensity of disturbance in a paddock of Digitaria eriantha, by georeferenced positions of a cow. Fecal abundance into 9 squares sampling sites of 144 m2 and coverage of Digitaria and native winter species before and after grazing period, in 3 permanent transects 10 m long by sector, were registered. To summarize the information of vegetation, INTECO was applied and forage availability was estimated in 9 samples of 0.5 m2 by sector. Fecal concentration gradually decreased getting away from the watering point. Digitaria coverage and forage availability after grazing period decreased in the 3 sectors, while in winter species just did it in nearby "C" and medium "M". The forage condition established by INTECO decreased one category after grazing period for sectors "C" and "M", in "L" (far) show a greater impact due to the entry of external animals. The geoposition of grazing animals lets to define a grazing gradient, and the studied variables support this effect. The position of grazing animals allows to define a grazing gradient, and the studied variables support this effect. The identification of grazing gradient regard to the watering point is paramount to improve the design of paddocks and water distribution, to enhance the efficiency of forage harvest.